Makna Ider Bumi pada Bulan Sura di Kelurahan Penataban Kecamatan Giri Banyuwangi - Sugianto, Iwan; Mardiana, Ninik; Faizin, Afan; Tahira, Ketin Ayu Heni (Jurnal Pendidikan Bahasa dan Sastra Indonesia Metalingua, 2024)
Penataban Village is one of the neighborhoods located in the center of Banyuwangi. Although situated in the center of Banyuwangi, Penataban Village continues to uphold traditional customs and cultural practices, such as the Ider Bumi ceremony. According to Kridalaksana (2023:13), meaning refers to the speaker's intention, the influence of language units in understanding human perception or behavior, relationships in terms of similarities or differences between language and non-language contexts, or between speech and all that it denotes, or the way language symbols are used. This study employs a qualitative research method. The data source for this research is the Ider Bumi event held during the Suro month in Penataban Village, Banyuwangi. The data focuses on the aspects of the meaning of Ider Bumi during the Suro month in Penataban Village, Banyuwangi. Data collection methods include (1) documentation, (2) note-taking, and (3) interviews. The Ider Bumi ceremony takes place both at night and in the morning. The meaning of the Ider Bumi ceremony in Penataban Village differs from that in other villages. The Ider Bumi event in Penataban is specifically held on the first day of Sura. In addition to the nighttime village procession, there is a communal meal held in the morning. This tradition is an essential part of the cultural and social identity of Penataban Village. The harmonious relationship between humans and nature is demonstrated through the communal meal, where residents come together to share food made from local produce. Furthermore, the harmonious relationship between humans and spirituality is reflected in the procession, which includes recitations of istighfar (a form of seeking forgiveness), the call to prayer, and prayers at every corner of the village